Influence of manganese oxide on the liquid-perovskite equilibrium in the CaO–SiO2–TiO2 system at 1400 °C in air. Issue 8 (15th April 2021) - Wan, Xingbang; Chen, Min; Qiu, Yuchao; Shi, Junjie; Li, Jianzhong; Liu, Changsheng; Taskinen, Pekka; Jokilaakso, Ari
Abstract: In the Selective Crystallization and Phase Separation (SCPS) process, manganese oxide is used as an additive to promote the precipitation of perovskite. However, the influence of manganese oxide on the liquid domain of the perovskite primary phase field is still unclear. In the present work, the liquid-perovskite equilibrium with the addition of 0–15 wt% Mn3 O4 was experimentally determined using a high-temperature isothermal equilibration-quenching technique, combined with X-Ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS) and Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS). It was confirmed that manganese was mainly existed as Mn 2+ and Mn 3+ in the molten phase, whereas titanium existed as Ti 4+ . Within the composition range of the present study, the 1400 °C liquid compositions varying from 0 wt% to 15 wt% Mn3 O4 overlapped significantly, mainly located at w (CaO)/ w (SiO2 ) ratios between 0.9 and 1.1. The isotherms simulated by FactSage, as well as the data from the literature, generally agreed well with the present experimental results. The calculated 1400 °C isotherms at different Mn3 O4 levels indicated that perovskite precipitation by manganese oxide was mainly promoted by increasing the Mn3 O4 concentration to expand the primary phase field of perovskite toward both higher and lower TiO2 content areas.